ANALISIS TINDAK PIDANA PENCUCIAN UANG DARI HASIL TINDAK PIDANA KORUPSI TERHADAP PENGADAAN BARANG DAN JASA (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 1793 K/PID.SUS/2014) - Tunggul Yohannes; Syafruddin Kalo; Sunarmi Sunarmi; Mahmud Mulyadi (Universitas Sumatera Utara, 2016)
ABSTRACT Corruption criminal act and money laundering criminal act were closely related. It can be seen in Article 2, paragraph 1 of Law No. 8/20120. Goods/service procurement is personal and functional responsibility. Functional responsibility is divided into PA (budget user)/KPA (Proxy of Budget User), PPK (Commitment Making Official), ULP (Procurement Service Unit)/Procurement Official, and the Committee/Official that Receives Work Outcome). Judicial analysis of money laundering criminal act on procuring goods/service (A Study on the Ruling of the Supreme Court No. 1793 K/PID.SUS/2014), showed that the judge’s consideration at the Medan District Court in handing down his verdict by stating that the defendant, Tono alias Asia, had been proven to commit criminal act as stipulated in Article 5, paragraph 1 in conjunction with Article 2, paragraph 1, letter a of Law No. 8/2011 on the Prevention and Eradication of Money Laundering Criminal Act, that the the judge’s imposition on the sanction was not appropriate since the defendant had collectively committed corruption criminal act as stipulated in the primary indictment under Article 2, paragraph 1 of Law No. 20/2001 in conjunction with Article 55, the first paragraph 1 of the Criminal Code. Keywords: Money Laundering, Corruption, Procurement